A kinesin family member 6 variant is associated with coronary heart disease in the Women's Health Study - Shiffman, Dov; Chasman, Daniel I; Zee, Robert Y L; Iakoubova, Olga A; Louie, Judy Z; Devlin, James J; Ridker, Paul M (Journal of the American College of Cardiology, 2008)
We asked if carriers of the 719Arg allele of kinesin family member 6 (KIF6) have increased risk of coronary heart disease (CHD) in a cohort of initially healthy Caucasian American women. The 719Arg allele of KIF6 (rs20455) has been reported to be associated with increased risk of CHD in a large population-based prospective study, ARIC (Atherosclerosis Risk in Communities), and in the placebo arms of 2 statin trials, CARE (Cholesterol and Recurrent Events) and WOSCOPS (West of Scotland Coronary Prevention Study). However, this KIF6 variant was not specifically investigated in the female subgroup in the ARIC study, and the CARE and WOSCOPS trials included only a small number of female patients. Genotypes of the rs20455 single nucleotide polymorphism (SNP) were determined among 25,283 initially healthy Caucasian women, age 45 years and older, participating in the WHS (Women's Health Study) who were prospectively followed over a 12-year period for incident cardiovascular events. The risk associated with the 719Arg allele of KIF6 was estimated using Cox proportional hazards models that adjusted for age and traditional risk factors. During follow-up, 953 women suffered a first-ever CHD event (myocardial infarction, coronary revascularization, or cardiovascular death) or first-ever ischemic stroke. Compared with noncarriers, carriers of the 719Arg allele had an increased risk of CHD (hazard ratio [HR] = 1.24 [95% confidence interval (CI) 1.04 to 1.46, p = 0.013]) and myocardial infarction (HR = 1.34 [95% CI 1.02 to 1.75, p = 0.034]) but not ischemic stroke. Confirming and extending previous reports, carriers of the 719Arg allele of KIF6 have 34% higher risk of myocardial infarction and 24% higher risk of CHD compared with noncarriers among 25,283 women from the WHS.